Respuesta :

Answer:

Answer:

[tex]{ \rm{ \hookrightarrow{ \blue{ {x}^{2} + 6x + 9 }}}} \\ { \rm{ \hookrightarrow{ \red{ {x}^{2} - 9 }}}}[/tex]

Step-by-step explanation:

» General Quadratic expression:

[tex] { \rm{y = {x}^{2} - (sum \: of \: roots)x + (product \: of \: roots)}}[/tex]

» For (-3, -3), roots are -3 and -3

Sum of roots:

[tex]{ \tt{sum = - 3 + - 3}} \\ { \tt{sum = - 6}}[/tex]

Product of roots:

[tex]{ \tt{product = - 3 \times - 3}} \\ { \tt{product = 9}}[/tex]

Equation:

[tex]{ \underline{ \underline{ \tt{ \: y = {x}^{2} + 6x + 9 \: }}}}[/tex]

» For (3, -3), roots are 3 and -3

Sum of roots:

[tex]{ \tt{sum = - 3 + 3}} \\ { \tt{sum = 0}}[/tex]

Product of roots:

[tex]{ \tt{product = - 3 \times 3}} \\ { \tt{product = - 9}}[/tex]

Equation:

[tex]{ \underline{ \underline{ \tt{ \: y = {x}^{2} - 9 \: }}}}[/tex]

The system of two quadratic equation is

x² + 6x + 9 = 0

x² - 9 = 0

What is a quadratic equation?

"A quadratic equation is an algebraic equation of the second degree in 'x'. The quadratic equation in its standard form is ax² + bx + c = 0, where 'a'(a ≠ 0) and 'b' are the coefficients, 'x' is the variable, and 'c' is the constant term."

The solution of the first equation in the system is (- 3, - 3).

Therefore, the equation will be

[x - (- 3)] [x - (- 3)] = 0

⇒ (x + 3)(x + 3) = 0

⇒ (x + 3)² = 0

⇒ x² + 6x + 9 = 0

The solution of the second equation in the system is (3, - 3).

Therefore, the equation will be

[x - 3] [x - (- 3)] = 0

⇒ (x - 3)(x + 3) = 0

⇒ (x)² - (3)² = 0

⇒ x² - 9 = 0

Learn more about quadratic equation here: https://brainly.com/question/16993652

#SPJ3